Modeling of kinematic characteristics of a mobile antenna of a spacecraft in a two-stage pivoting device - Yury N. Gorelov; Lubov V. Kurganskaya (Вестник Самарского университета: Естественнонаучная серия)
The problem of calculating the kinematic characteristics of a mobile antenna device (AD) based on the specified values of kinematic characteristics of the line of sight (LS) "spacecraft — information reception point" in the associated coordinate system of the spacecraft is considered. The kinematic characteristics of the AD in the form of the current values of its rotation angles and angular velocities and accelerations (according to the corresponding control channels) are determined from the conditions for combining the LS with the axis of the directional diagram of the AD for the case of a two-stage pivoting device with mutually orthogonal axes of rotation of the AD.